Clinical features and outcome of lymphoma patients with pre‐existing autoimmune diseases. (5th December 2017) - Shih, Yu‐Hsuan; Yang, Youngsen; Chang, Kuang‐Hsi; Chen, Yi‐Hsing; Teng, Chieh‐Lin Jerry
Abstract: Aims: Previous epidemiological studies have shown that autoimmune diseases increase the risk of lymphoma development. However, whether autoimmune diseases deteriorate the outcomes for lymphoma patients remains unclear. This study aimed to identify the clinical features of lymphoma patients with pre‐existing autoimmune diseases. Whether pre‐existing autoimmune diseases impacted progression‐free survival (PFS) and overall survival (OS) in lymphoma patients was further investigated. Methods: We retrospectively reviewed medical records of 913 newly diagnosed lymphoma patients from January 2008 to November 2016. Thirty‐four lymphoma patients with pre‐existing autoimmune disorders were identified. Six of these 34 patients were lost to follow‐up; their data was used to examine baseline clinical characteristics but not survival. Therefore, 28 lymphoma patients with autoimmune diseases were included in the autoimmune disease group for comparing the remission rate, PFS and OS to lymphoma patients without autoimmune diseases (control group; n = 56). Results: Diffuse large B‐cell lymphoma was the most common histological subtype (18/34; 52.94%). Complete remission rates in the autoimmune disease and control groups were 72.0% and 83.3%, respectively ( P = 0.178). Patients with and without autoimmune diseases had similar PFS (45.4 ± 59.9 months vs . 51.5 ± 42.8 months; P = 0.398) and OS (46.4 ± 52.6 months vs . 50.1 ± 47.3 months; P = 0.352). By univariate analysis, pre‐existing autoimmune diseases were not associated with inferior PFS ( P = 0.326) or OS ( P = 0.627). Conclusions: Lymphoma patients with and without autoimmune disorders had comparable outcomes. Autoimmune diseases are not an obstacle to lymphoma treatment.